Biocompatibility of nanometre scale porous anodic aluminium oxide membranes towards the RK 13 epithelial cell line: A preliminary study - Poinern, Gérrard Eddy Jai; Le, Xuan Thi; O’Dea, Mark; Fawcett, Derek (International Journal of Research in Medical Sciences, 2017)
Background: This study for the first time examines the biomedical potential of using anodic aluminium oxide (AAO) for culturing Oryctolagus cuniculus (European Rabbit) Kidney (RK-13) epithelial cells. Methods: The cellular response of RK-13 cells towards in-house synthesised AAO membranes, a commercially available membrane and glass controls were investigated by examining cell adhesion, morphology and proliferation. The in-house membranes were anodized using a two-step procedure to produce a highly ordered hexagonal pore and channel structure. Results: Cell proliferation over a 48 h period indicated that the AAO membranes were more than comparable with the glass control substrates. Subsequent microscopy observations revealed evidence of focal adhesion sites and cellular extensions interacting with the underlining porous membrane surface structure. Conclusions: The study has shown that AAO membranes have the potential to culture RK-13 cells and indicate a possible tissue engineering technique for producing tissues.